2016
DOI: 10.1088/1741-2560/13/3/036002
|View full text |Cite
|
Sign up to set email alerts
|

A novel semi-immersive virtual reality visuo-motor task activates ventrolateral prefrontal cortex: a functional near-infrared spectroscopy study

Abstract: The present study has revealed a particular involvement of the VLPFC in the execution of the novel proposed semi-immersive VMT adoptable in the neurorehabilitation field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 97 publications
1
16
0
Order By: Relevance
“…The changes of HbO 2 /Hb level in the VLPFC appeared to have followed the demand of visuo‐motor interactions, being modest upon the game onset and becoming larger after the first encounter. The results are, therefore, consistent with the notion that VLPFC activations during video game playing may be a response to visuo‐motor processes .…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The changes of HbO 2 /Hb level in the VLPFC appeared to have followed the demand of visuo‐motor interactions, being modest upon the game onset and becoming larger after the first encounter. The results are, therefore, consistent with the notion that VLPFC activations during video game playing may be a response to visuo‐motor processes .…”
Section: Discussionsupporting
confidence: 88%
“…Early studies reported positive DLPFC activation during game‐like cognitive tasks, which was modulated by game difficulty . However, there are also many previous studies reporting DLPFC deactivations during virtual reality visuo‐motor tasks and active video game playing . The deactivation of DLPFC appeared to be modulated by the genre of the game, but not the age or the performance level of the player .…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations